2014
DOI: 10.1155/2014/819052
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Left Atrial Myxoma

Abstract: Atrial myxomas are the most common primary cardiac tumors. Patients with left atrial myxomas generally present with mechanical obstruction of blood flow, systemic embolization, and constitutional symptoms. We present a case of an unusually large left atrial myxoma discovered incidentally in a patient with longstanding dyspnea being managed as bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…However, multiple atrial, biatrial, atrioventricular, and biventricular tumors have been reported. 1 , 2 The usual size is 0.4–6.5 cm. Symptoms may result from valvular obstruction or emboli but may also be non-specific or absent.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple atrial, biatrial, atrioventricular, and biventricular tumors have been reported. 1 , 2 The usual size is 0.4–6.5 cm. Symptoms may result from valvular obstruction or emboli but may also be non-specific or absent.…”
Section: Discussionmentioning
confidence: 99%
“…About 70% of all myxomas originate in the LA, 20% in the right atrium, and 5% can be present in both. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Some authors like Medhat have reported myxomas of 7.7 × 5.5 × 3.7 cm. 5 Parameswaran et al . 9 published a case with a myxoma of 11 cm weighing 105 g. Most myxomas range from 1 to 6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of cardiac myxomas are surgical with very successful results. (7,10,11) We believe that taking the result of echocardiography which is a simple technique, into consideration will be life saving in order not to miss out the reasons beneath respirotary disordered patients.…”
Section: Discussionmentioning
confidence: 99%